2006
DOI: 10.1007/s10725-006-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a cDNA-encoding ACC synthase and its mRNA expression during zygotic embryogenesis of chick-pea (Cicer arietinum L.) seeds

Abstract: Plant hormones play many important roles in plant growth and development. We previously tried to control barley (Hordeum vulgare L.) flowering in ear cultures treated with plant hormones and related compounds, and found that anther extrusion from florets was reduced by treatment with 100 ppm methyl jasmonate (MJA). In the present study, we show that 10 ppm MJA also inhibits anther extrusion in barley ear cultures. Spraying field-grown barley ears with MJA clarified the efficacy of this chemical under field con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It should also be mentioned that MeJA sometimes triggers cleistogamy, which can reduce sterility under heat stress conditions (Honda, Seto, Turuspekov, Watanabe, & Yoshida, 2006;Koike et al, 2015). Because PTSGMS rice lines are total male sterility at higher temperature (>23°C), we argue that cleistogamy could not occur as MeJA is applied or MeJA concentration is increased in spikelets of these lines under HT stress.…”
Section: Discussionmentioning
confidence: 79%
“…It should also be mentioned that MeJA sometimes triggers cleistogamy, which can reduce sterility under heat stress conditions (Honda, Seto, Turuspekov, Watanabe, & Yoshida, 2006;Koike et al, 2015). Because PTSGMS rice lines are total male sterility at higher temperature (>23°C), we argue that cleistogamy could not occur as MeJA is applied or MeJA concentration is increased in spikelets of these lines under HT stress.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, the expression of OeACS2 and OeACO2 in olive AZ was reduced by CoCl 2 in the non-abscising cultivar, while CoCl 2 had little or no effect on the abscising cultivar. In the latter, the repression of OeACS2 expression did not coincide with the changes of ACC content, perhaps because of post-transcriptional or translation regulation on ACS in olive fruit AZ as seen in other tissues of other species ( Gomez-Jimenez and Matilla, 2006 ). The analysis of gene expression following application of ET biosynthesis inhibitors at the onset of fruit ripening demonstrated that the expression of OeERS1 is negatively regulated by ET at this stage in olive fruit AZ–AC tissue.…”
Section: Discussionmentioning
confidence: 92%
“…It is suggested that MeJA could trigger cleistogamy sometimes in cereals, which can reduce sterility under heat stress conditions (Honda et al, 2006;Koike et al, 2015). As mentioned previously, a PTSGMS rice line shows totally male sterility under HT during anthesis; cleistogamy could not occur as MeJA is applied to PTSGMS rice lines under HT stress.…”
Section: Discussionmentioning
confidence: 93%